STUDI KINETIKA CURING DARI RESIN PHENOL-FORMALDEHID DENGAN MODIFIER SODIUM METASILIKAT - M. Wahyu Sya'bani; Warmiati Warmiati; Kutut Aji Prayitno (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2016)
This study aims to obtain the curing kinetics of modified PF resin using sodium metasilicate. Three process steps are involved; polimerization of PF resin, thermal analysis and evaluation. In polimerization, phenol and formaldehyde are reacted with sodium hidroxide or sodium metasilicate as catalyst in batch reactor. Dynamic kinetics are done by calculating the heat flow during curing process using Differential Scanning Calorimetry (DSC). The temperature and heatflow data obtained at peak exotherm curve are used for calculating the kinetics. Resin structures are studied using FT-IR and SEM. The calculation result show that the activation energy (Ea) is 105.100 J/mol for PF resin with sodium metasilicate and 118.070 J/mol for PF resin without modifier. Whereas, FTIR analysis shows that there are O-H, aldehyde and C=C aromatics functional groups as the structures of PF Resin. The lower value of activation energy and curing temperature indicates the sodium metasilicate is potential as modifier for PF Resin.